Applied High-Resolution Geophysical Methods Offshore Geoengineering Hazards - Trabant, Peter K. (Springer Netherlands, 1984)
The discipline encompassing the use of high-resolution geophysics for obtaining geoengineering survey data has evolved rapidly over the past decades to become an interdisciplinary subject encompassing the fields of Geophysics, engineering, geology, marine geology, oceanography, and civil engineering. While high-resolution geophysical surveys are routinely performed offshore today, this has been so only since the late 1960s. High-resolution geophysical methods are employed in the offshore environment to obtain a comprehensive picture of the sea-floor mor phology and underlying shallow stratigraphy. The purpose of the survey methods is to assist in the design and installation of bottom-supported structures such as drilling and production platforms and pipelines. Drilling structures and pipelines of steel and/or concrete have become behemoths with respect to their size and the complexity of their design in order to withstand, for periods of up to twenty-five years, an extremely harsh environment, including storm waves, strong currents, unstable sea floor conditions, and great water depths. It is therefore of paramount importance that the geometry and physical properties of the sea floor be well understood in order to provide an adequate foundation for the design lives of such structures. On land, engineering foundation data usually may be obtained by visual field inspection and shallow borehole information, but offshore the presence of the water column places certain constraints on geoengineering investigations. High-resolution geophysical methods employed in the acquisition of geoengineering data offshore are defined as the use of seismic sources and receivers that operate at acoustic frequencies greater than 100 Hz